SUMBER-SUMBER ILMU PENGETAHUAN DALAM PERSPEKTIF ISLAM DAN BARAT - Nawazir, Safrudin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this paper is to find out the sources of knowledge in Islamic and Western perspectives. This research uses library research. The results of the study show that: sources of knowledge from Islam come from the AlQur'an, Assunnah / hadith of the Prophet Muhammad SAW, Reason, Revelation, inspiration, five senses, experience, intuition etc. In Western epistemology, there are three ways to acquire knowledge: First, the rationalist approach. An understanding that knowledge occurs because of material given to the five senses and the mind which is processed by "reason". Second, empiricism, namely an understanding which argues that the knowledge obtained is limited only to experience. Third, dualism, this understanding seeks to combine or reconcile the two poles of understanding that are diametrically opposed.